2011
DOI: 10.3109/15622975.2011.597875
|View full text |Cite
|
Sign up to set email alerts
|

A pilot genome wide association and gene expression array study of suicide with and without major depression

Abstract: Objectives Suicide is partly heritable but the responsible genes have not been identified. We conducted a gene-centric, low coverage single nucleotide polymorphism (SNP) pilot genome-wide association study (GWAS) seeking new candidate regions in suicides with and without depression, combined with gene expression assay of brain tissue. Methods Ninety-nine Caucasian subjects, including 68 who completed suicide and 31 who died suddenly from other causes, were genotyped postmortem using GeneChip® Mapping 50K Xba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 39 publications
0
57
0
Order By: Relevance
“…First, postmortem findings identified that MDD patients show a strong dysregulation of immune system pathways in the brain, encompassing altered levels of pro- and anti-inflammatory cytokine expression of IL-1α, IL-2, IL-3, IL-5, IL-8, IL-9, IL-10, IL-12A, IL-13, IL-15, IL-18, IFN-γ and lymphotoxin-α (12). Similarly, altered mRNA levels of immune system genes were found in the neocortex of subjects who committed suicide (58, 59). Second, the immune deficits appear to be systemic in patients with MDD, and that they are readily detectable in the peripheral tissues (2).…”
Section: Discussionmentioning
confidence: 94%
“…First, postmortem findings identified that MDD patients show a strong dysregulation of immune system pathways in the brain, encompassing altered levels of pro- and anti-inflammatory cytokine expression of IL-1α, IL-2, IL-3, IL-5, IL-8, IL-9, IL-10, IL-12A, IL-13, IL-15, IL-18, IFN-γ and lymphotoxin-α (12). Similarly, altered mRNA levels of immune system genes were found in the neocortex of subjects who committed suicide (58, 59). Second, the immune deficits appear to be systemic in patients with MDD, and that they are readily detectable in the peripheral tissues (2).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the samples / cohorts used for GWAS on suicidality outcomes reviewed here were better ascertained and homogenous in relation to psychiatric diagnoses (mainly MDD and BPD), with one exception (Galfalvy et al, 2013). This meant that the case-control comparisons did not reflect SNP-association with those psychiatric disorders (as being controlled for by its presence in both case and controls), but with the suicidality outcomes per se.…”
Section: Conclusion and Future Considerationsmentioning
confidence: 97%
“…The following limitations are also noteworthy: the samples were not primarily designed to study suicide attempts, the definitions of suicide attempt may have differed between and within cohorts, information about the severity / repetition / intent of the suicide attempts was missing, only testing SNPby-SNP GWAS and that the main finding only bordered to genome-wide significance. Galfalvy et al (2013 but with e-pub already 2011 November 7) published what is the first and yet only available GWAS on completed suicides, using an alternative approach termed as a "pilot". Controls were sudden deaths by other causes than suicide.…”
Section: Suicidal Behavior Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Although these have mostly produced inconclusive or inconsistent results, it is notable that such approaches facilitate an un biased analysis of molecular pathways that are implicated in disease and are an important method to use. For example, a GWAS identified 14 single-nucleotide polymorphisms (SNPs) that were associated with treatmentemergent suicidal ideation in patients who had been treated with antidepressants 30 , and another study examining suicide completers identified seven genes that were differentially expressed in suicide completers compared with control individuals but not in individuals with mood disorders 35 . However, most of the GWASs used fairly small samples that lacked the power to detect effects other than major gene effects and their results require confirmation.…”
Section: Distal or Predisposing Factorsmentioning
confidence: 99%